Stories of special young: a rereading from a community perspective - Travaglini, Alessia (Formazione & insegnamento, 2018)
Nowadays the concept of talent and merit is at the center of a broad discussion: in particular, we ask if and how institutions, firstly schools, should and could take initiatives aimed to raise and develop it. Starting from an analysis of the etymological meaning of terms such as talent and meritocracy, the article aims to investigate the relationship between individuals and communities in the genesis and promotion of talent. The re-reading of Malala Yousafzai and Iqbal Masih biographies, two young Pakistani activists who have spent their lives in improving the conditions of their peers and in implementing a more fair world, provides the opportunity for focusing on educational models and widespread formative approaches in current teaching practices.